Overcoming the digital divide through the promotion of digital reading - Wilson, Tom; Maceviciute, Elena (Qualitative and Quantitative Methods in Libraries, 2019)
Inequalities in access and use of information and communication technologies are usually labelled the digital divide, which implies a strong gap between those who have access and use technologies and those who do not. The public library can play a significant role in enabling a society in overcoming the divide, which is a consequence of inequalities in the distribution of wealth, and the consequent inequalities in access to the appropriate technologies and networks. This paper describes an ongoing project in Lithuania, which aims to test the possibilities of digital reading as means of overcoming the digital divide.